CASE SERIES : LIVER ABSCESSES MIMICKING NEOPLASMS AND RUPTURED INTO ANTERIOR ABDOMINAL WALL AND PLEURAL CAVITY - TAHER, M.A. (The ASEAN Journal of Radiology, 2023)
We like to report two cases of liver abscesses in two men of 27 and 38 years of age, the younger one presented as a cauliflower-like fungating ulcer extending from the right hypochondrium to the right iliac fossa, the later one presented with brown cough and fever. Both the patients were followed up to clinical cure. One of them had serial ultrasonography and radionuclide scans also.